Hebräisch oder Griechisch? - Mulzer, Martin (Biblische Notizen, 2025)
As for the question of the original language of the greek writings of the Old Testament there is a clear answer in the case of Sirach (Hebrew) and Wisdom (Greek). In Tobit the decision between Hebrew and Aramaic remains open. Recent research assumes a Greek original for Judith, which is also suggested here for 1 Maccabees. 2 Maccabees as a whole, including the letters at the beginning, is considered Greek. Both parts of Baruch, chap. 1-5, and the Letter of Jeremiah, chap. 6, were also written in Greek.